Optimizing low temperature storage techniques for extending avocado shelf-life - Kamble, Vittal; Narayana, C. K.; Rao, D. V. Sudhakar (Indian Horticulture, 2025)
Avocado fruit is rapidly gaining popularity among Indian farmers, traders and consumers due to its high nutritional value, more health benefits and increased international trade. As Avocado is a minor crop in India, not much information is available on its cultivation and postharvest handling. Climacteric nature of avocado fruit makes it ripe within a week after the harvest. Critical temperatures for cold storage of avocados are standardized in countries like Mexico, Brazil, USA and Peru, where it is grown at a commercial scale. However, storage temperature differs among the growing areas and cultivars. In India, avocado cultivation is especially picking up pace in southern states because of its high price and more demand in the market. However, the shorter shelf life and lack of information on optimum storage temperature result in increased postharvest loss and lower profit to growers and traders. Hence, understanding fruit physiology and knowing the optimum low temperature for cold storage are imperative crucial to extend the shelf-life of avocado fruits for longer duration with better fruit quality and least spoilage.